Investasi Emas Online pada Aplikasi Marketplace Tokopedia dalam Perspektif Fikih Muamalah - Syamsiah Nur; Muftiha Aulia Rahmah N (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2022)
This study aims to determine law of online gold investment in the Tokopedia marketplace application in perspective of muamalah fiqh. This research is a library research using a juridical and normative approach. In analyzing the data, the researcher used content analysis. Results of this study are the practice of online gold investment carried out at Tokopedia Emas based on a study of general arguments sourced from the Qur'an, and specific arguments from the hadith and the views of the mu'tabar scholars of the four schools of thought considered invalid/unlawful. because it does not fulfill the muamalah contract, namely the absence of the handover of goods (gold). Implication of this research is the public can know and understand the shari'a views on gold investment in the Tokopedia marketplace application so that Muslims will always prioritize the precautionary principle that comes from a knowledge in investing in gold.